Role of Music in a Plastic Surgery Setting: A Systematic Review and Meta-analysis - James A. Zapata-Copete; Maria Juliana Cordoba-Wagner; Herney Andrés García-Perdomo (Indian Journal of Plastic Surgery, 2019)
Objective To assess the effectiveness and harm of music to reduce anxiety and pain in a plastic surgery setting. Materials and Methods A search strategy was conducted in the MEDLINE, CENTRAL, EMBASE, and LILACS databases. Searches were also conducted in other databases and unpublished literature. Clinical trials were included without language restrictions. The risk of bias was evaluated with the Cochrane Collaboration’s tool. An analysis of random effects was conducted. The primary outcomes were anxiety and pain. The secondary outcomes were length of stay, physiological parameters, and adverse effects. The measure of the effect was the mean difference (MD) and standardized MD (SMD) with a 95% confidence interval (CI). The planned interventions were music versus no music. Results Four articles were included in the qualitative and quantitative analysis. A total of 306 patients were found among the four studies. A low risk of bias was shown for most of the study items. The overall standardized mean difference (SMD) for anxiety -3.64 [95%CI -5.71 to -1.56 (p-value = 0.0006)] favoring music compared with no intervention, and for pain the mean difference (MD) was -12.06 [95%CI -33.47 to 9.35 (p-value = 0.2696)] showing no statistical differences. Conclusion Playing music is a safe and free intervention that diminishes anxiety in patients who undergo plastic surgery procedures.